Amino acids in the vitreous and intravitreal fluid in rhegmatogenous retinal detachment patients with different proliferative vitreoretinopathy grades - G.V. Levitskaya (Ukrainian Society of Ophthalmologists, 2015)
Background:Proliferative vitreoretinopathy (PVR) is known to worsen the treatment prognosis of rhegmatogenous retinal detachment (RRD) and to result in irreversible loss of vision due to apoptotic or necrotic process in retinal neurons. Some studies have tried to examine the role of amino acids (first of all, neurotransmitters) in the development of proliferative vitreoretinopathy (PVR). Glutamate is known to cause migration and proliferation of RPE and/or glial cells. Based on this fact, it has been hypothesized that antagonists of glutamate may prevent or reduce the intensity of these processes. Additionally, it has been proved that elevated vitreous glutamate levels in proliferative diabetic retinopathy are potentially toxic to retinal ganglion cells, and that elevated vitreous levels of gamma-aminobutyric acid and glutamate promote the development of vasoproliferative processes. In general, little is still known about the role of immune acids and that of the imbalance in their levels in the pathogenesis of retinal pathology, and the importance of the issue of PVR complications is of no doubt. Purpose: To investigate the features of the distribution of amino acids in the vitreous and intravitreal fluid in patients with RRD with different PVR grades. Materials and Methods: Eighty-eight patients (88 eyes) were ofthalmologically examined and underwent surgery for RRD. Gas-liquid chromatography was utilized to determine the levels of 15 amino acids in vitreous and intravitreal fluid samples obtained at the time of vitrectomy and fluid-gas exchange to provide tamponade, respectively. Data were analyzed taking into account the PVR grade (grades A, B and C in 11, 64 and 13 patients, respectively). Results: In RRD patients, the levels of amino acids under study in the vitreous and, especially, in intravitreal fluid increased significantly with the increase in PVR grade to grade B. If the PVR continued to progress to grade C, a tendency to decrease in the neurotransmitter levels was observed, but they remained statistically significantly higher than those in grade A. Significant correlations were revealed between PVR grade and amino acid levels in intravitreal fluid, and, in most cases, in the vitreous. Further progression of the proliferative process was accompanied by a higher increase in the levels of excitatory amino acids (aspartate and glutamic acid), than that of the inhibitory one (glycine). Conclusion: The data presented provide evidence for the role of elevated amino acid (first of all, neurotransmitter) levels in the development of proliferative processes in RRD. The imbalance found in the levels of excitatory and inhibitory neurotransmitters (aspartate and glutamic acid vs. glycine) results in the excitotoxic effect, and creates pathochemical preconditions for retinal degeneration.